Conceptual basis of sportsmanship improvement among qualified boxers - Gatin, F. A.; Kolesnik, I. S. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. Boxing demands special system of sports training and it is conditioned by its orientation to the skills of active confrontation with the opponent mastering using powerful striking actions, which cause hard pain senses and a high probability of getting trauma. It helps to consider this kind of sport as a kind of life school, which uses boxing means for volitional, intellectual spheres improvement, many-sided development, a complex influence on the functional systems, which increases reserve abilities of an individual, his readiness to successful socialization and effective labor activity. Materials. Choosing boxing as the means for the level of physical and technical readiness increase is conditioned by the degree of this kind of sports activity correspondence with the abilities and opportunities of an organism, target setting at the ways of personal development. The article offers the approach to technical readiness improvement among qualified boxers on the basis of the leading conceptual theses realization. Research methods:scientific-methodical literature analysis, progressive pedagogical experience of the trainers and highly-qualified boxers, summarizing; pedagogical experiment, testing, mathematical material handling. Results. The leading conceptual theses use helps not only to define the character of physical activity, but also to influence on a boxer`s consciousness in order to develop his intellectual, moral and volitional potential. An integral approach to the training process organization provides the necessity understanding to give a sportsman`s personal development the first place, a sportsman`s development who is able to fulfill an objective estimation of own influences. The results of the pedagogical experiment showed the effectiveness of the offered methodology and it was proved in higher indices of physical and technical readiness. Conclusion. Created by the author methodology of sports training improvement among qualified boxers is directed at personal and motional-coordinating qualities development, which correspond to the specificity of boxing; at the skills of volitional potential formation by means of quickness of motional reactions improvement, orientation in spatio-temporal and spatio-power parameters of motional actions; at a weaker hand development till it becomes the leading one; at the skills of a precise moment determination to use each technique.